International Editorial Board of vol. 14, 2018, Journal Scientific and Applied Research: International Editorial Board of vol. 14, 2018, Journal Scientific and Applied Research - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
International Editorial Board of vol. 14, 2018, Journal Scientific and Applied Research